Dynamic aikido - Shioda, Gozo
Ancient theory, modern practice: Dynamic aikido brings together the whole spectrum of theoretical and applied aikido. Through it, one can become perfectly attuned to his opponent, can sense his intentions and turn his movement to one's own advantage. Comprehensive and fully illustrated, Dynamic Aikido presents the basic postures and stances, fundamental techniques and applications : how to cope with frontal attack, how to avoid an attack from the rear, how to sense thwart the pickpocket. An essential companion for every beginner, a vital reference for students of all levels